Life history of wahoo, Acanthocybium solandri, in the Tropical Eastern Atlantic Ocean – the importance of applying a suite of methods for fisheries assessment in data-limited situations - Kindong Richard; Wu Feng; Sarr Ousmane; Dai Libin; Tian Siquan; Dai Xiaojie (Oceanological and Hydrobiological Studies)
Unassessed fisheries, mostly non-targeted fisheries, are now particularly predominant in many commercial fisheries and are critical to food security in developing countries. These fisheries typically lack reliable data essential for assessing their stocks, leaving them susceptible to overfishing and declining yield over time. This study proposes a framework for determining the life history and management of such fisheries. Data on the length composition and reproduction of wahoo Acanthocybium solandri, a common bycatch species in commercial fisheries, were obtained from observers aboard Chinese longline vessels in the Eastern Atlantic between 2010 and 2020 and were used as a case study. A comprehensive methodological approach was applied using data on this species to estimate its life history parameters, to evaluate biological reference points, and to provide proxies for the stock status. The final main growth parameters obtained were: Linf = 161.21 cm FL (157.34–194.68), K = 0.47/year (0.14–0.65); estimated size at first maturity was 89.6 cm FL. As assessed by the set of methods applied, the wahoo stock state was healthy in the Tropical Eastern Atlantic Ocean. This study advises against using a single approach to determining life history parameters in data-limited fisheries, as this may affect reference points and thus management recommendations. This study provides a route whereby many easy-to-apply methods can be used to understand the status of multiple stocks in poorly managed fisheries, and thus provide management plans.